Tata Kelola dan Kebijakan Pengawasan Birokrasi Pemerintah Jawa Barat dalam Pelaksanaan Program Pembinaan Anak di Barak Militer - Edward Benedictus Roring (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study analyzes the supervision carried out by the West Java Provincial Government on the implementation of the juvenile delinquency development program through military barracks initiated by Governor Kang Dedi Mulyadi (KDM). This program aims to form the character of discipline and responsibility of problematic children through a militaristic approach. The research method uses a juridical-normative approach and policy studies with analysis of official documents and interviews with relevant stakeholders. The results of the study indicate that provincial government supervision plays an important role in ensuring program implementation in accordance with the principles of child protection and character education standards. However, there are significant challenges related to the potential for violations of children's rights and the controversy over the harsh approach applied. This study recommends strengthening humanistic and participatory supervision mechanisms so that the development program can run effectively without ignoring children's rights. This study provides normative and practical contributions to the development of policies for the development of juvenile delinquency development in West Java that are oriented towards a balance between discipline and child protection.